Effects of total soft tissue and shell thickness on the accumulation of heavy metals (Cd, Cu, Pb, and Zn) in the green-lipped mussel Perna viridis - Yap, C. K.; Ismail, A.; Tan, S. G. (undefined, 2003)
The effects of the total soft tissue dry weight and shell thickness and on the accumulation of Cd, Cu, Pb, and Zn were determined in the green-lipped mussel Perna viridis. In agreement with Boyden's formula (1977), our results showed that the plotting of metal concentrations against the total soft tissue dry weight and shell thickness of the mussel on a double logarithmic basis gave negative coefficients especially for Cd, Pb, and Zn. Therefore, the smaller mussels (lower total soft tissue dry weight) had higher concentrations of Cd, Pb, and Zn than the larger ones. Since shell thickness could be considered to estimate of the age of the mussel, it was also found that the younger mussels accumulated more Cd, Pb, and Zn than the older ones. This indicated that P. viridis has a different metabolic strategy for each of the metals studied which may be related to age. However, the accumulation of Cu was hardly affected by the sizes and ages of the mussel. This indicated that the accumulation pathways of Cu and the processes affecting the bioavailability of Cu to the mussel are different from those for Cd, Pb, and Zn. © 2003 MAIK "Nauka/Interperiodica".